P211 Domiciliary care of patients with primary and secondary pneumothoraces: Our experience in Ayrshire, patient satisfaction and health economic analysis. (14th November 2013) - Guhan, A; Learmonth, S; Moseley, O; Sword, D; Kelly, F
Abstract : Background: Domiciliary care (DC) of Spontaneous Pneumothoraces (SP) with an ambulatory Heimlich Valve (HV) attached to the Intercostal Chest Drain (ICD) has potential for care-closer-to-home, avoiding hospitalisation and saving healthcare resources. Wider acceptance of this practice requires demonstration of tangible benefits in terms of patient safety, patient satisfaction and cost savings. Method: In the last year (since July 2012), we established a consultant-led DC service for SP at the University Hospital Ayr, Ayrshire. All primary (PSP) or secondary (SSP) SP admitted through The Emergency Department (ED) were assessed within 48 hours for potential DC with informed consent, based on presence of Persistent Air Leak and predetermined criteria ensuring patient safety (Table:1). All DC patients had 72 hourly consultant ward reviews (CWR) with chest Xray or sooner should patients identify HV non-movement with coughing. ICD was removed when SP resolved. SP patients on DC were readmitted if concerns were identified. Patient satisfaction was assessed formally (Table 6). Health economics: Costs were calculated from an NHS perspective by examining resource use associated with DC for SP. This figure was then compared against the potential cost-avoidance in terms of respiratory medicine bed days saved. Costs were taken from published ISD reference costs when available and local finance teams, staff costs include the full cost to the organisation including superannuation (13%) and national insurance contributions. Results: 8(33.3%) of 24 SP were discharged from ED. 16(PSP : SPS = 7 : 9) were admitted; 10 (62.5%) accepted to have DC. Please see the results tabulated. Conclusions: Carefully organised DC for SP is safe, cost effective and meets with high patient approval and satisfaction.